PELATIHAN BUDIDAYA MAGGOT BSF MENGGUNAKAN LIMBAH ORGANIK RUMAH TANGGA KEPADA POKDAKAN DESA KULO - Muhammad Bibin; Erfina Erfina; Sundari Sundari; Lukman Lukman; Khaeriyah Adri; Ahmad Mustanir; Sunandar Said; Astrini Padapi; Barisan Barisan; Buhari Buhari (Jurnal Abdi Insani, 2025)
The issue of household organic waste and the high cost of fish feed remains a significant challenge in Kulo Village. Limited community knowledge and skills in managing organic waste with economic value exacerbate this situation. A training program on Black Soldier Fly (BSF) larvae cultivation using household organic waste was implemented as a solution to both the waste problem and the rising cost of fish feed in Kulo Village, Sidenreng Rappang Regency. This initiative targeted the Anugrah Fishery Group (Pokdakan), which lacks expertise in organic waste management through BSF maggot bioconversion. This community empowerment program aimed to enhance the knowledge and skills of Pokdakan Anugrah in cultivating BSF maggots by utilizing household organic waste as a waste management solution and an alternative fish feed source. The methodology consisted of three phases: (1) outreach and introductory instruction on waste management and maggot cultivation, (2) hands-on practice in constructing BSF egg-laying cages and media, and (3) evaluation through pre-test and post-test assessments. The evaluation results indicated a substantial improvement in participants’ understanding, increasing from an initial 35.92% to 93.30% across various aspects, including the role of maggots as decomposers, the use of “kasgot” as fertilizer, maggots as alternative fish feed, the BSF life cycle, and cultivation techniques. The program demonstrated the potential to reduce household organic waste volume, lower fish farming production costs, and create new economic opportunities through the sale of maggots and organic fertilizer. The training activities significantly improved participant comprehension. Post-test scores increased to 90.62%–95.25% compared to the pre-test scores of 33.50%–38.50%. Participants directly practiced the fermentation of BSF maggot substrate using 10–15 kg of organic waste, constructed multi-level bioponds, BSF fly cages, and egg-laying media. This program not only has the potential to reduce household organic waste but also enables the production of highly nutritious alternative fish feed, thus reducing aquaculture production costs by 60–70% compared to conventional feed. Additionally, new economic opportunities may emerge through the sale of fresh/dried maggots and kasgot organic fertilizer. Overall, this training successfully empowered Pokdakan Anugrah in a sustainable manner, supported environmental management efforts, and fostered the development of a waste-based creative economy.